The evaluation of learning in university classrooms: a research on the practices (Praxis Educativa, 2017)
The present work describes a research carried out as a Master thesis work, on the subject of the evaluation of learning at university. The objective of the research was to study the formative evaluation practices that exist in an institution of engineering education, to make them visible. It was started from the conception of formative evaluation as one that is integrated to the teaching and that allows the feedback. It was developed with a qualitative methodology based on interviews with students, teachers and an institutional reference, plus analysis of various documents. As a result, five cases of formative assessment practices were selected and analyzed, and common conclusions were reached
Keywords: evaluation of learning; formative evaluation; qualitative research; college